2004
DOI: 10.1038/nn1300
|View full text |Cite
|
Sign up to set email alerts
|

PI3K promotes voltage-dependent calcium channel trafficking to the plasma membrane

Abstract: Phosphatidylinositol 3-kinase (PI3K) has been shown to enhance native voltage-dependent calcium channel (Ca(v)) currents both in myocytes and in neurons; however, the mechanism(s) responsible for this regulation were not known. Here we show that PI3K promotes the translocation of GFP-tagged Ca(v) channels to the plasma membrane in both COS-7 cells and neurons. We show that the effect of PI3K is mediated by Akt/PKB and specifically requires Ca(v)beta(2) subunits. The mutations S574A and S574E in Ca(v)beta(2a) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
194
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(204 citation statements)
references
References 38 publications
8
194
1
1
Order By: Relevance
“…7) is consistent with the hypothesis that impaired LTCC trafficking contributes to the reduction in I Ca,L density in diabetic myocytes. Our results are also consistent with a model proposed by Viard et al (13) in which PI(3,4,5)P 3 activation of Akt results in phosphorylation of the LTCC ␤2a-subunit, which leads to increased trafficking of the channels to the cell surface. It was reported that the neuronal N-type Ca 2ϩ channel rapidly internalized and reappeared on the cell surface after GABA receptor stimulation within 80 s (34).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…7) is consistent with the hypothesis that impaired LTCC trafficking contributes to the reduction in I Ca,L density in diabetic myocytes. Our results are also consistent with a model proposed by Viard et al (13) in which PI(3,4,5)P 3 activation of Akt results in phosphorylation of the LTCC ␤2a-subunit, which leads to increased trafficking of the channels to the cell surface. It was reported that the neuronal N-type Ca 2ϩ channel rapidly internalized and reappeared on the cell surface after GABA receptor stimulation within 80 s (34).…”
Section: Discussionsupporting
confidence: 93%
“…PI(3,4,5)P 3 and insulin stimulation of I Ca,L is blocked by taxol treatment. It was reported that activation of PI 3-kinase stimulates I Ca,L density through Akt-mediated phosphorylation of ␤2a-subunits, leading to increased trafficking of exogenously expressed LTCC to the plasma membrane in COS7 cells (13). We hypothesized that PI(3,4,5)P 3 infusion stimulates trafficking of the LTCC to the cell surface of diabetic cardiac myocytes, thus increas- ing I Ca,L density.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is the dominantly expressed Ca v 1.2 b-subunit in the heart. The phosphatidylinositol-3-kinase pathway is-via interaction with Ca v b2-involved in ensuring a sufficient expression of Ca v 1.2 on the plasma membrane [Viard et al, 2004].…”
Section: Brs4-mutations In Cacnb2mentioning
confidence: 99%
“…Phosphorylation sites on the ␣ 1 subunit were invoked for PKA (6 -8), CaMKII (9 -11), PKG (12,13), Akt/PKB (14,15), and by PKC (16 -19). In addition, phosphorylation sites in the Ca v ␤ 2 subunit were reported for PKA (20) at Ser 479/480 (rabbit protein sequence (rbs)) (21), CaMKII (22) at Thr 500 (rbs), PKG (12) at Ser 496 (rbs), and Akt/PKB (14,15,23,24) at Ser 576 (rbs). The amino acids modified by protein kinases in Ca v ␤ 2 or Ca v 1.2 in the protein sequence from rabbit, rat, and mouse are listed in supplemental Table 1.…”
mentioning
confidence: 99%